High resolution melting versus sequenciamento genético de nova geração na detecção de mutação do gene KRAS em câncer colorretal - Miranda, Raelson Rodrigues [UNIFESP] (2017)
Introduction: Frequency of KRAS gene mutations in colorectal cancer is around 34% and confers poor prognosis. The most frequency are on exon 2, 3 and 4. The knowledge about KRAS profile plays crucial role in the management of this disease, because the use of MABs like cetuximab and panitumumab are recommended exclusively for KRAS wild-type tumors. In other words, it has important predictive value. PCR-High-Resolution melting (HRM) analysis is a novel technology able to detect mutations with high sensitivity through of variations in melting temperature of DNA with low cost than sequencing methods. Therefore, could be a good tool for screening of KRAS mutations. Objective: Comparing capacity of HRM to detect exons 2, 3 and 4 KRAS mutations with Next Generation Sequencing. Methods: We performed PCR-HRM runs for 47 patients with confirmed colorectal adenocarcinoma in StepOne plus Real-time PCR (Thermo-Fisher/Life Technology©) and compared the melting temperature and HRM curve between mutated and wild-type groups. We used the Illumina HiSeq platform® as reference methods for the Next Generation Sequencing. The statistical analysis was performed through SPSS software v20.1. Results: For exon 2, the melt curves were different between mutant and wild-type groups. The mean of melting temperature was 78.13 ºC for wild-type and 77.87 ºC for mutant profile (p= 0.001; CI 95%: 0,11-0,41; T-test). Sensitivity was 93.8%, specificity 96.6%, PPV 92.2%, NPV 98.51%, accuracy 91.5% and false positive and negative rates 3,4% for PCR-HRM. In terms of exons 3 and 4, melt curve were not different. Conclusions: In this study, the high resolution melting curve profile proved be a good test for screening of exon 2 KRAS mutations in colorectal cancer with high sensitivity and specificity. However, for exons 3 and 4, HRM was not able to detect mutations.